Transactional information systems theory, algorithms, and the practice of concurrency control and recovery - Weikum, Gerhard; Vossen, Gottfried (San Francisco : Morgan Kaufmann, 2002)
Transactional Information Systems is the long-awaited, comprehensive work from leading scientists in the transaction processing field. Weikum and Vossen begin with a broad look at the role of transactional technology in today's economic and scientific endeavors, then delve into critical issues faced by all practitioners, presenting today's most effective techniques for controlling concurrent access by multiple clients, recovering from system failures, and coordinating distributed transactions. The authors emphasize formal models that are easily applied across fields, that promise to remain valid as current technologies evolve, and that lend themselves to generalization and extension in the development of new classes of network-centric, functionally rich applications. This book's purpose and achievement is the presentation of the foundations of transactional systems as well as the practical aspects of the field what will help you meet today's challenges. * Provides the most advanced coverage of the topic available anywhere--along with the database background required for you to make full use of this material. * Explores transaction processing both generically as a broadly applicable set of information technology practices and specifically as a group of techniques for meeting the goals of your enterprise. * Contains information essential to developers of Web-based e-Commerce functionality--and a wide range of more "traditional" applications. * Details the algorithms underlying core transaction processing functionality.
PART ONE -- BACKGROUND AND MOTIVATION -- Chapter 1 What Is It All About? -- Chapter 2 Computational Models -- PART TWO -- CONCURRENCY CONTROL -- Chapter 3 Concurrency Control: Notions of Correctness for the Page Model -- Chapter 4 Concurrency Control Algorithms -- Chapter 5 Multiversion Concurrency Control -- Chapter 6 Concurrency Control on Objects: Notions of Correctness -- Chapter 7 Concurrency Control Algorithms on Objects -- Chapter 8 Concurrency Control on Relational Databases -- Chapter 9 Concurrency Control on Search Structures -- Chapter 10 Implementation and Pragmatic Issues -- PART THREE -- RECOVERY -- Chapter 11 Transaction Recovery -- Chapter 12 Crash Recovery: Notion of Correctness -- Chapter 13 Page Model Crash Recovery Algorithms -- Chapter 14 Object Model Crash Recovery -- Chapter 15 Special Issues of Recovery -- Chapter 16 Media Recovery -- Chapter 17 Application Recovery -- PART FOUR -- COORDINATION OF DISTRIBUTED TRANSACTIONS -- Chapter 18 Distributed Concurrency Control -- Chapter 19 Distributed Transaction Recovery -- PART FIVE -- APPLICATIONS AND FUTURE PERSPECTIVES -- Chapter 20 What Is Next?
Includes bibliographical references (p. 791-827) and index.
Keywords: Transaction systems (Computer systems); Electronic books